Lung Tissue Resident Memory T-Cells in the Immune Response to Mycobacterium tuberculosis - Ogongo, Paul; Porterfield, James Zachary; Leslie, Alasdair (Frontiers in Immunology, 2019)
Despite widespread BCG vaccination and effective anti-TB drugs, Tuberculosis (TB) remains the leading cause of death from an infectious agent worldwide. Several recent publications give reasons to be optimistic about the possibility of a more effective vaccine, but the only full-scale clinical trial conducted failed to show protection above BCG. The immunogenicity of vaccines in humans is primarily evaluated by the systemic immune responses they generate, despite the fact that a correlation between these responses and protection from TB disease has not been demonstrated. A novel approach to tackling this problem is to study the local immune responses that occur at the site of TB infection in the human lung, rather than those detectable in blood. There is a growing understanding that pathogen specific T-cell immunity can be highly localized at the site of infection, due to the existence of tissue resident memory T-cells (Trm). Notably, these cells do not recirculate in the blood and thus may not be represented in studies of the systemic immune response. Here, we review the potential role of Trms as a component of the TB immune response and discuss how a better understanding of this response could be harnessed to improve TB vaccine efficacy.